Shape dependent heat transport through green synthesized gold nanofluids. (16th July 2015) - John, Jisha; Thomas, Lincy; Rajesh Kumar, B; Kurian, Achamma; George, Sajan D
Abstract: Nanofluids hold promise as a more efficient coolant for thermoelectric devices. Despite the capability of tailoring the thermo physical properties of nanofluids, by tuning the particle parameters such as shape, size and concentration, the toxicity of chemicals used for the preparation of nanoparticles is a serious concern. Green synthesis of nanoparticles is emerging as an alternative to the conventional chemical and physical methods for the preparation of nanoparticles. In this work, the results of the preparation of gold nanoparticles using plant extracts as reducing agents are presented. The green synthesis route employed for the present study provides particles of similar size, but the shape of the particles is found to vary depending upon the source of the natural reducing agents. The thermal diffusivity values of the gold nanofluid measured using laser based dual beam thermal lens technique elucidate the role of shape and concentration of the green synthesized nanoparticles on the effective thermal diffusivity values of the nanofluids.